"Ceaseless Poverty"?: Image and the Poietic Word. Issue 3 (5th December 2013) - Ziarek, Krzysztof
Abstract : Looking at Dickinson and Hölderlin, this essay begins by exploring the idea of the poetic dimension of existence and its relation to the image, or more precisely, to the capability to disclose into images. For Dickinson the relentless "poverty" of a non-poetic existence indicates that what is missing from such existence are not just images but the capacity for their "disclosing" - the poetic gift or aptitude. With the help of Heidegger's essays on poetry and poverty, I invert this relation between image and poverty to show that, even though the inceptive character of the poetic word and the element of poetic dwelling it allows to emerge appear poor in comparison to images or concepts, it is the poetic word that for the very first time lets humans dwell. Although it can neither boast the richness of "pictures" nor the strength and precision of conceptual comprehension, the poetic is what opens up the world for humans and simultaneously opens their being to its characteristic manner of inhabiting this world.